Deregulating Teacher Labor Markets - Simon Burgess; Ellen Greaves; Richard J. Murphy (Institute of Labor Economics (IZA), 2019)
A common feature of public sector labor markets is the use of pay scales. This paper examines how the removal of pay scales impacts productivity, by exploiting a reform that compelled all schools in England to replace pay scales with school-designed performance related pay schemes. We find that schools in labor markets with better outside options for teachers saw relatively higher increases in teacher pay. Schools in these areas relatively increase their spending on teachers, have higher teacher retention and larger improvements in student tests scores. These effects are largest in schools with the high proportions of disadvantaged students. We conclude that the pay rigidities in the form of centralized pay schedules result in a misallocation of resources, by preventing such schools from retaining their teachers.
Keywords: J33; I28; 330; pay scales; teachers; performance related pay; productivity